Primary Intraosseous Schwannoma in Tibial Epiphysis With Unique Immunohistochemical Phenotype: A Case Report. (September 2014) - Wang, Tao; Giugale, Juan M.; Ding, Ming; Goodman, Mark A.; Schoedel, Karen; Rao, Uma N. M.
Schwannoma is a benign peripheral nerve sheath neoplasm of soft tissue that consistently demonstrates immunohistochemical staining for S100 protein. Intraosseous location of schwannoma is very uncommon. We report the first case of an intraosseous schwannoma located in the epiphysis of tibia in an adult patient. Radiologically, it mimicked a primary bone tumor and despite benign histological appearance, the tumor eroded cortical bone. Morphologically on routine stains and electron microscopy it has features of a schwannoma. But by immunohistochemistry, the tumor was positive for both desmin and S100 protein in the same region.